Health problems of tamaulipas's farm workers employed with h-2a visas in the United States - Izcara Palacios, Simón Pedro; Andrade Rubio, Karla Lorena (Centro de Historia Argentina y Americana, 2011)
From two decades ago Tamaulipas' farm workers have received a large amount of H-2A visas to work in the farming sector. U.S. farmers find it appealing to hire Tamaulipas' workers because of the proximity of Tamaulipas to the frontier, which lowers transportation costs, which have to be paid by the employers. It is well reported that low-skilled guest worker programs leaves foreign workforce open to abuse and exploitation. Poor compliance with federal regulations like the Worker Protection Standard and Workers Compensation Insurance increases the risk of pesticide poisoning and injuries among agricultural workers, and those who suffer work-related injuries or illnesses forgo needed medical care. This paper examines the health problems suffered by Tamaulipas's H-2A workers employed in U.S. agriculture.